Influence of Pyroligneous Acid on Fermentation Parameters, CO2 Production and Bacterial Communities of Rice Straw and Stylo Silage - Guo, Xiang; Zheng, Peng; Zou, Xuan; Chen, Xiaoyang; Zhang, Qing (Frontiers in Microbiology, 2021)
CO2 is a primary greenhouse gas and the main cause of global warming. Respiration from plant cells and microorganisms enables CO2 to be produced during ensiling, a method of moist forage preservation applied worldwide. However, limited information is available regarding CO2 emissions and mitigation during ensiling. Pyroligneous acid, a by-product of plant biomass pyrolysis, has a strong antibacterial capacity. To investigate CO2 production and the influence of pyroligneous acid, fresh stylo and rice straw were ensiled with or without 1% or 2% pyroligneous acid. Dynamics of the fermentation characteristics, CO2 production and bacterial communities during ensiling were analyzed. Pyroligneous acid increased the lactic acid content and decreased the weight losses, pH, ammonia-N content, butyric acid content and coliform bacterial numbers (all P < 0.05). It also increased the relative abundance of Lactobacillus and decreased the relative abundances of harmful bacteria such as Enterobacter and Lachnoclostridium. Adding pyrolytic acids reduced the gas production, especially of CO2. It also increased the relative abundances of CO2-producing bacterial genera and of genera with the potential for CO2 fixation. In conclusion, adding pyroligneous acid improved the fermentation quality of the two silages. During ensiling, CO2 production was correlated with bacterial community alterations. Using pyroligneous acid altered the bacterial community to reduce CO2 production during ensiling. Given the large production and demand for silage worldwide, application of pyroligneous acid may be an effective method of mitigating global warming via CO2 emissions.